Analisis Pendapatan dan Ketahanan Pangan Petani Terdampak Erupsi Gunung Sinabung di Kawasan Relokasi Siosar Kabupaten Karo, Sumatera Utara - Hotden Leonardo Nainggolan; Albina Ginting (AGRIMOR, 2022)
Food security is an important issue that must be considered by all parties to date, both at the central and regional levels. This study aims to analyze the income and level of food security of farmers affected by the eruption of Mount Sinabung in the Siosar relocation area, Sub-district of Tiga Panah, Karo District. The research was conducted from July to November 2021. The data used in this study were primary and secondary data which were analyzed descriptively. Based on the results of the study concluded; a) The average income of farmers from potato, cabbage and sweet potato farming is IDR22,606,740.62/planting periode or IDR5,651,685.16/month; b) There are 23.3% who earn outside farming, with an average income of IDR556,928.57/month; c) The average expenditure of farmers for food consumption is IDR911,902.33/month or IDR3,647,609.33/ planting periode; d) Farmers' average expenditure for non-food consumption is IDR647,103,20/month or IDR 2,588,412,70/ planting periode; e) There are 43% of farmers with the proportion of food expenditure > 60.0%, with an average food consumption expenditure of IDR898.336.00/month; f) The total food and non-food expenditure of farmers is IDR1,156,490/month, with an average proportion of farmer spending 77.68%/month, then the proportion of food expenditure of farmers is to be high (> 60% of the total expenditure of the farmer's family), is categorized as not food security; g) There are 57% of farmers with the proportion of food expenditure < 60.0%, with an average food expenditure of IDR 922,276.00/month; h) The total food and non-food expenditure of farmers is IDR1,866,924/month, and the average proportion of non-food expenditure of the respondent is 49.40%/month, then the proportion of food expenditure of farmers is low (<60% of total expenditure of the farmer's family ), then the degree of food security is categorized as food security.